Implementing Innovative Social Investment Strategic Lessons from Europe - Baines, Susan; Bassi, Andrea; Csoba, Judit; Sipos, Flórián (Policy Press, 2019)
The turn towards a Social Investment approach to welfare implies deploying resources to enhance human capital and mobilise the productive potential of citizens, starting in early childhood. This edited collection brings regional and local realities to the forefront of social investment debates by showcasing successes, challenges and setbacks of Social Investment policies and services from ten European countries: Italy, UK, Sweden, Finland, Greece, Germany, Poland, the Netherlands, Hungary, and Spain. It provides practical, accessible illustrations of good practice, routes to success, and lessons learned. The book is informed throughout by engagement with service users and local communities, and features many previously unheard voices including front-line workers, local decision makers, volunteers and beneficiaries.